Design of control systems of unmanned aerial vehicles via a vicon motion capture system - A. V. Davtyan (ՀՀ ԳԱԱ հրատ.)
In the paper, an approach to the design of control systems of Unmanned Aerial Vehicles (UAVs) using the Simulink graphical package and the Vicon Motion Capture (MOCAP) System is discussed. Դիտարկված է անօդաչու թռչող ապարատների (ԱԹԱ-ների) կառավարման համակարգի նախագծման մոտեցում՝ օգտագործելով Simulink գրաֆիկական ծրագրավորման միջավայրը և Vicon շարժումը գրանցող (MOCAP) համակարգը: Рассмотрен подход к проектированию систем управления беспилотных летательных аппаратов (БПЛА) с использованием графического пакета Simulink и системы захвата движения Vicon.
Keywords: Technology